2005
DOI: 10.1159/000088461
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Marinobufagenin in a Rat Model of Human Preeclampsia

Abstract: Background: Preeclampsia is a potentially devastating disorder of hypertension in pregnancy for which there is currently no definitive treatment short of delivery. The bufadienolide, marinobufagenin (MBG), an inhibitor of Na+/K+ ATPase, has been found to be elevated in extracellular fluid volume-expanded hypertensive patients, a condition similar to preeclampsia. Thus, these studies sought to examine the role of MBG in our rat model of preeclampsia. Methods and Results: Pregnant female ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 59 publications
8
67
0
Order By: Relevance
“…Specific antibodies against MBG prevent both the acute and sustained NaCl-induced increase in arterial pressure (10). A prohypertensive effect of SPI in response to salt loading in hypertensive prone rats has been repeatedly observed (9,10,12,13,29). Our results show that a subacute increase in dietary NaCl elicits a sustained increase in MBG that is directly related to an increase in renal FENa and inversely related to NaCl sensitivity of SBP in population of normotensive middle-age and older women.…”
Section: Discussionsupporting
confidence: 56%
“…Specific antibodies against MBG prevent both the acute and sustained NaCl-induced increase in arterial pressure (10). A prohypertensive effect of SPI in response to salt loading in hypertensive prone rats has been repeatedly observed (9,10,12,13,29). Our results show that a subacute increase in dietary NaCl elicits a sustained increase in MBG that is directly related to an increase in renal FENa and inversely related to NaCl sensitivity of SBP in population of normotensive middle-age and older women.…”
Section: Discussionsupporting
confidence: 56%
“…In an animal model of preeclampsia, we have shown that urinary excretion of MBG is elevated prior to the development of hypertension indicating that it may play a key role in the pathogenesis of preeclampsia (7). In addition, administration of an anti-MBG antibody corrected the deoxycorticosterone acetate-salt hypertension in pregnant rats, which demonstrated elevated urinary excretion of MBG (7,8). These findings suggest that MBG might affect first trimester CTB function.…”
Section: Marinobufagenin (Mbg)mentioning
confidence: 73%
“…Preeclampsia is associated with shallow placentation, inadequate invasion, and insufficient remodeling of the maternal arteries (13,15). In an animal model of preeclampsia, we have shown that urinary excretion of MBG is elevated prior to the development of hypertension indicating that it may play a key role in the pathogenesis of preeclampsia (7). In addition, administration of an anti-MBG antibody corrected the deoxycorticosterone acetate-salt hypertension in pregnant rats, which demonstrated elevated urinary excretion of MBG (7,8).…”
Section: Marinobufagenin (Mbg)mentioning
confidence: 88%
See 1 more Smart Citation
“…149 In pregnant rats rendered hypertensive by deoxycorticosterone acetate and salt supplementation, uterine arteries exhibited enhanced sensitivity to the vasoconstrictor action of marinobufagenin, and an antimarinobufagenin antibody had an antihypertensive effect. 150 Thus, it appears that increases in circulating marinobufagenin levels are responsible for the Na + /K + -ATPase inhibition induced by preeclampsia and contribute to the pathogenesis of pre-eclampsia. Accordingly, low concentrations of marinobufagenin impair the differentiation of the cytotrophoblast in vitro.…”
Section: Role Of Cardiotonic Steroids In Pre-eclampsiamentioning
confidence: 99%